Ask questions and get helpful answers.

consider the functions g(x)=(4-x^2)^0.5 and h(x)=(x^2)-5.

find the composite functions hog(x) and goh(x), if they exist, and state the domain and range of the composite functions.


ok, i have figured out that hog(x)=-1-X^2, but in my answer booklet it says that the domain of this function is -2<&=x<&=2, and the range is -5<&=y<&=-1. can someone please explain how i can get this answer??thanks

and i have no idea why the function goh(x) does not exist. help please!

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩
2 answers
  1. hog(x) means that you first perform the function g(x), and then enter the result of that function as x in the second function h(x).
    The function g(x) is a square root, meaning that whatever is under the square root sign has to be positive (you can't take the square root of a negative number).

    4-x^2 is only positive if -2 <= x <= 2, so this is the domain of g(x) and since x can take on any value in h(x), it's also the domain of hog(x).

    Now, for the range, we have to check when h(x) takes on its largest and smallest values. When we draw the graph of x²-5, we notice that it is a parabole. We can easily determine that for x=0, the parabole will reach its lowest point, and then starts to rise again. Since the maximum value for x is 2 or -2, we check that for 2 or -2 h(x) reaches the value -1 (being its largest value for -2 <=x <= 2).
    So the range of hog(x) is -5<=y<=-1.

    As for goh(x), it does exist. if we replace every x in g(x) by h(x), we get goh(x). Since 4-(x²-5)² is only positive for -sqrt(7) until -sqrt(3) and from sqrt(3) untill sqrt(7), this function only has values in those places.
    So the domain of goh(x) = [-sqrt(7),-sqrt(3)] U [sqrt(3),sqrt(7)].

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  2. write h(x) as composition of two functions h(x) = (fog)(x)

    h(x) = 3 square root 7 + 3 square root of x

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Similar Questions

  1. Calculus

    Write the composite function in the form f(g(x)). [Identify the inner function u = g(x) and the outer function y = f(u).] (Use non-identity functions for f(u) and g(x)). y = tan(x^5) (f(u),g(x))=(?) I thought the answer would be (tan(x),x^5) but it turns

  2. Calculus

    Assume that x and y are functions of t and x^2+2xy=5. If dx/dt=-3 when x=-1, find dy/dt

  3. Algebra

    1.) Describe the relationship of input and output values for composite functions. 2.) Explain how you know if a radical expression is in simplest form. 3.) How can you tell if radicals are like radicals?

  4. Mathematics

    Suppose that the functions p and q are defined as follows. p(x)=-x-1 q(x)=-2x^2-2 Find the following. (pxq)(5) (qxp)(5)

  5. Calculus

    Suppose y = sqrt(2x + 1), where x and y are functions of t. (a) If dx/dt = 15, find dy/dt when x = 4. dy/dt = ?

  6. 11th grade maths

    A.give an example of a function whose domain is {3,4,7,9}? and whose range is {-1,0,3} B.Find two different functions whose domain is {3,8}and whose range is {-4,1} C Explain why there does not exist a function whose domain is {-1,0,3} and whose range is

  7. Check my CALCULUS answers please!

    Any short explanation for things I got wrong would be great, too, if possible! Thanks in advanced! :) 8. Which of the following functions grows the fastest? ***b(t)=t^4-3t+9 f(t)=2^t-t^3 h(t)=5^t+t^5 c(t)=sqrt(t^2-5t) d(t)=(1.1)^t 9. Which of the following

  8. English

    Which of the following describes a gerund and how it functions in a sentence?(1 point) A gerund is a verb ending in -ing that functions as a noun in a sentence. A gerund is a verb ending in , -ing, that functions as a noun in a sentence. A gerund is a noun

  9. Simpson's rule

    Is the simpson's rule always more accurate than the midpoint rule and trapezoidal rule? Not always; it is possible that the midpoint and/or trapezoidal rule determine exact values. 1. Some functions values for a function f are given below. x 0 0.5 1.0 f(x)

  10. Mathematics

    Suppose that the functions p and q are defined as follows. p (x) = -x 2 q (x) = -2x +2 Find the following. (p×q)(-5) (q ×p)(-5)

Still need help?

You can ask a new question or browse existing questions.